Selpercatinib in RET fusion-positive non-small-cell lung cancer (SIREN): a retrospective analysis of patients treated through an access program. (June 2021) - Illini, Oliver; Hochmair, Maximilian Johannes; Fabikan, Hannah; Weinlinger, Christoph; Tufman, Amanda; Swalduz, Aurélie; Lamberg, Kristina; Hashemi, Sayed M. S.; Huemer, Florian; Vikström, Anders; Wermke, Martin; Absenger, Gudrun; et al.
Introduction: Rearranged during transfection (RET) gene fusions are rare genetic drivers in non-small cell lung cancer (NSCLC). Selective RET-inhibitors such as selpercatinib have shown therapeutic activity in early clinical trials; however, their efficacy in the real-world setting is unknown. Methods: A retrospective efficacy and safety analysis was performed on data from RET fusion-positive NSCLC patients who participated in a selpercatinib access program (named patient protocol) between August 2019 and January 2021. Results: Data from 50 patients with RET fusion-positive advanced NSCLC treated with selpercatinib at 27 centers in 12 countries was analyzed. Most patients were Non-Asian (90%), female (60%), never-smokers (74%), with a median age of 65 years (range, 38–89). 32% of the patients had known brain metastasis at the time of selpercatinib treatment. Overall, 13 patients were treatment-naïve, while 37 were pretreated with a median of three lines of therapy (range, 1–8). The objective response rate (ORR) was 68% [95% confidence interval (CI), 53–81] in the overall population. The disease control rate was 92%. The median progression-free survival was 15.6 months (95% CI, 8.8–22.4) after a median follow-up of 9 months. In patients with measurable brain metastases ( n = 8) intracranial ORR reached 100%. In total, 88% of patients experienced treatment-related adverse events (TRAEs), a large majority of them being grade 1 or 2. The most common grade ⩾ 3 TRAEs were increased liver enzyme levels (in 10% of patients), prolonged QTc time (4%), abdominal pain (4%), hypertension (4%), and fatigue/asthenia (4%). None of patients discontinued selpercatinib treatment for safety reasons. No new safety concerns were observed, nor where there any treatment-related death. Conclusions: In this real-world setting, the selective RET-inhibitor selpercatinib demonstrated durable systemic and intracranial antitumor activity in RET fusion-positive NSCLC and was well tolerated.